Estudio comparativo de resultados cefalométricos digitales vs resultados de cefalométricos manuales (2021)
Cephalometry is an important tool to diagnose the squeletal class and facial growth, so you can make a correct treatment plan. Digital and manual methods exhibit significant differences for SNA, SNB and 1Inf-NB angular measurements, with the manual method being determined to have a higher average than the digital method in these three measures. No significant differences were evident for any of the linear measurements between the averages observed using the digital method and the manual method.